Cancer pain in children and adolescents - Kram, Mirosława; Kurylak, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2006)
As far as population of growth age is concerned, every year, in Poland there are 1100 to 1300 new cases of going down with cancer. The most common cases are leukemia, tumour, lymphoma (59.3% of all children’s cancer cases). Current treatment is based on multidrug chemotherapy, which is the basis of the oncological treatment. Radiotherapy and surgery are only supplementary methods. Pain is an integral part of cancer disease. “Cancer pain” is used to describe pain caused by cancer which occurs as a result of antitumour therapy and both situations simultaneously. Difficulty of estimation of occurrence frequency and pain intensity as far as children of different ages are concerned resulted in development of many scales. Current methods of estimation of pain intensity are based on nonverbal information and verbal one, which describe pain features. More than one instrument should be used to make the estimation valid. Each scale should be earlier explained to the patient. Visual Analogue Scale- VAS is the basic scale and it is used to estimate pain as far as children over 5 years old are concerned. Number Rating Scale – NRS is a variety of VAS. It is suitable for children over 7 years old, as well as Verbal Rating Scale VRS (word scale) and scale according to Oucher. In the latter, pictures of child’s faces are used. Maps of pain are an additional source of information about pain – a child ticks places which hurt. APPT is a self-report instrument for children aged 7-17. DEGR is a behavioural-observational scale which was created to estimate long lasting pain as far as children aged 2-6 are concerned. AOB – a form which contains a number of words describing pain which the patient is currently suffering from or the last pain. The form is suitable for children over 11 years old and it contains pain estimation in quantitative and qualitative categories